Superexpressão dos genes GmGlb1-1 e GmEXPA-1 aplicada ao aumento de tolerância do algodoeiro a Meloidogyne incognita - Araújo, Gabriele Louise Trindade (2024)
The cotton crop is exploited by various industries, especially the textile industry, playing a significant role in the global economy. Nematodes of the genus Meloidogyne pose a challenge to economically important crops such as cotton. They induce feeding sites on plant roots that impair water and nutrient uptake, leading to reduced crop yields. Current control methods are ineffective, and developing less susceptible cultivars is the most efficient and sustainable strategy for managing this phytopathogen. Glycine max genes, GmGlb1-1, involved in nitric oxide metabolism, and GmEXPA1, related to cell wall lignification processes, are responsive to Meloidogyne incognita parasitism. Independent overexpression of these genes resulted in reduced susceptibility of Arabidopsis thaliana and Nicotiana tabacum plants to M. incognita. With the aim of developing cotton plants less susceptible to M. incognita using advanced breeding techniques, this study simultaneously overexpressed GmGlb1-1 and GmEXPA1 genes via Agrobacterium tumefaciensmediated transformation. Plants from five independent transgenic events in the T2 generation, characterized by PCR and enzyme-linked immunosorbent assays showing high accumulation of transgenic proteins, were inoculated with 2,000 M. incognita ppJ2 juveniles 15 days after germination in a greenhouse bioassay. After 90 days, roots were evaluated for gall incidence using a qualitative rating scale and eggs per gram of root. Gene expression analyses and determination of transgene copy numbers in plants were conducted. Progenies from two transgenic events showed a significant reduction of up to 82% in eggs per gram of roots compared to non-transformed plants. The three events with the greatest reduction in egg numbers also had the highest transgene expression levels, reinforcing the relationship between transgene overexpression and reduced susceptibility. All transgenic events exhibited the insertion of three copies of the T-DNA. The results demonstrate successful heterologous expression of soybean genes in cotton, indicating species compatibility for proper transgene processing. Additionally, high genetic and protein conservation of target genes with cotton's endogenous orthologs was observed, suggesting potential new biotechnological tools for future study. Thus, overexpression of GmGlb1-1 and GmEXPA1 genes can be considered a potential strategy in developing biotechnological cultivars with reduced susceptibility to root-knot nematodes for more sustainable and less pesticide-dependent agriculture.